Overconfidence Behavioral Bias in Working Capital Management and Performance of Small and Medium Enterprise in Ghana : A Conceptual Paper - Lamptey, Jeff; Asri, Marsidi; Bilyaminu, Usman; Ashemi, Baba Ali (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2020)
The concept of overconfidence is well understood in financial market and corporate decision as individual investors and managers of large corporations prone to overconfident bias. This paper is the first to conceptualize overconfidence bias in working capital management and performance of Small and medium enterprise by employing qualitative case study inquiry to gain insight and small and medium enterprise (SME) managers overconfident behavioral. This paper argues that overconfidence bias can distorts working capital investment with the possibility of overinvestment working capital inventory if SME managers have enough internal equity in anticipation of higher performance.